Dimensions of diversity as communicated through institutional mission and diversity statements: a review of institutions in the Big 12 conference - DeCuir, Danielle M. (Kansas State University, 2010)
Diversity in higher education plays an important role in students’ perspectives on their college experiences. For students looking for an institution that has a diverse living and learning environment, it is important that students can find information related to diversity. This report highlighted dimensions of diversity as communicated through mission and diversity statements from institutions in the Big 12 Conference. The Big 12 Conference institutions include Baylor University, Iowa State University, Kansas State University, Oklahoma State University, Texas A&M University, Texas Tech University, University of Colorado – Boulder, University of Kansas – Lawrence, University of Missouri, University of Nebraska, University of Oklahoma, and the University of Texas. The institutions’ mission and/or diversity statements were evaluated using the four dimension of diversity: access and success, climate and intergroup relations, education and scholarship, and institutional viability and vitality. The results of this report alert students, faculty, and staff, as well as the institution, about the aspects of diversity being developed at their institution and in which dimensions they need further development.
Keywords: diversity; diversity statement; mission statement; Education, Administration (0514); Education, Higher (0745)